Croatian translation and validation of the Mind-Wandering Questionnaire (MWQ) - Perković Kovačević, Marina (Array, 2020)
This research aimed to translate and validate the Mind-Wandering Questionnaire (MWQ) to the Croatian language, and to provide preliminary data on its reliability, factor structure and convergent validity in a sample of Croatian students. After translation and adaptation, the Croatian version of the MWQ was administered to 451 eight-grade elementary school students (239 female and 212 male participants). With the MWQ, we administered the Emotional Skills and Competence Questionnaire (ESCQ-45). Results show high internal consistency of the Croatian translation of the MWQ. Confirmatory factor analysis supports an unidimensional model. Convergent validity was supported by a significant negative correlation between MWQ and Emotional Skills and Competence Questionnaire. We propose further investigation of psychometric properties of the Croatian translation of the MWQ and investigating test-retest reliability as well as discriminant validity of the Questionnaire.